RANCANG BANGUN SISTEM MONITORING SUHU AIR, KETINGGIAN AIR, DAN KADAR TDS LARUTAN NUTRISI PADA TANGKI HIDROPONIK BERBASIS INTERNET OF THINGS - Saputra, Andhika Rahmat; Maulana, Eka; Nurussa’adah, n/a (Jurnal Mahasiswa TEUB, 2024)
Hydroponic cultivation is a cultivation technique that utilizes water as a growing medium. The advantages of hydroponic techniques include a low possibility of pest attacks, efficient land use, soilless plant growth, increased quantity and quality of production, and better cleanliness compared to conventional agriculture. In hydroponic cultivation, important aspects to be considered are the availability of water, water temperature, and the Total Dissolved Solids (TDS) level in the nutrient solution flowing through the plant roots. In practice, manual monitoring of water availability, water temperature, and TDS levels in the nutrient solution in hydroponic tanks becomes an issue for farmers at Happy Tani farm. Manual data monitoring leads to irregular data recording, hindering the maximization of hydroponic system productivity. To address this issue, a study was conducted to design an Internet of Things-based monitoring system capable of detecting water temperature, water level, and TDS levels in hydroponic tanks. This system involves DS18B20 sensors for detecting water temperature, Ultrasonic AJ-SR04M sensors for detecting water level, and DFRobot Gravity TDS sensors for detecting TDS levels in the nutrient solution. The system can provide real-time measurement data and tank condition alerts to farmers through an Android application or website connected to the internet. The system also features datalogging on a Google Spreadsheet website for storing measurement data at regular intervals. The research involved system design, sensor testing, TDS level measurement, data transmission, and hydroponic tank condition alert systems. The results of this research indicate that the designed system is capable of transmitting data to the application and website, providing tank condition alerts, and accurate data measurement with error rates for DS18B20 sensors at 0.69%, Ultrasonic AJ-SR04M sensors at 0.5%, DFRobot Gravity TDS sensors for EC at 3.16%, and TDS at 3.37%. Keywords: hydroponic, monitoring, water temperature, water level, total dissolved solids, Internet of Things